Pengaruh Digital Tranformation, Asset Intensity, dan Employee Intensity terhadap Cost Stickiness Dimoderasi oleh Ukuran Perusahaan - Mutiara Nurani; Hexana Sri Lastanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The economic instability caused by the Covid-19 pandemic has resulted in a deceleration of economic growth in Indonesia. Consequently, corporate management needs to judiciously manage costs to ensure the sustainability of the company. Many companies continue to face significant burdens amidst declining sales, indicating the presence of cost stickiness within the companies. This study aims to investigate the impact of digital transformation, asset intensity, and employee intensity on cost stickiness in the manufacturing industry. It employs a quantitative research approach utilizing secondary data extracted from the financial reports of companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The sample comprises 73 manufacturing companies. Data analysis is conducted using Eviews version 10. The findings reveal that digital transformation, asset intensity, and employee intensity collectively account for 8.3% of the variance in cost stickiness, while the remainder is influenced by other factors not examined in this study. Therefore, managerial decisions regarding cost management are crucial for the company's sustainability.